On the reduction principle in the theory of stability of motion - Lykova, O. B. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
This paper deals with the development of Lyapunov's idea of reducing the problem of stability of the trivial solution of a system of higher-order differential equations to a similar problem for a system of lower order. Special attention is paid to the application of integral manifolds and approximate integral manifolds.